Influence of platelet rich fibrin on post-extraction socket healing: A clinical and radiographic study - Alzahrani, Ahmed Abdullah; Murriky, Afraa; Shafik, Sami (The Saudi dental journal, 2017)
The aim of this study was to evaluate clinically and radiographically, extraction socket healing using autologous platelet rich fibrin (PRF). Twenty-four subjects needing single tooth simple extractions were selected. Twenty-four extraction sockets were divided into test group (PRF, n=12) and control group (blood clot, n=12). PRF was prepared with blood drawn from individuals after extraction using standard technique. PRF was placed in test group sockets followed by pressure application and figure 8 sutures. Sockets in control group were allowed to heal in the presence of blood clot and received a figure 8 suture. Ridge width was assessed using cast analysis with the help of acrylic stent and a pair of calipers. Radiographic analysis of socket surface area was performed using computer graphic software program. The clinical follow up assessments were performed at 1, 4 and 8weeks. Collected data was assessed using ANOVA and multiple comparisons test. Subjects were aged between 25 and 50 (mean 37.8) years, including 15 females. The mean horizontal ridge width for sockets in the test group were 11.70±2.37mm, 11.33±2.30mm and 10.97±2.33mm at 1, 4 and 8weeks respectively. Ridge width proportions were significantly higher among test group as compared to control group between baseline to 4 and 8weeks respectively. The mean radiographic bone fill (RBF) percentage in the test group, was 74.05±1.66%, 81.54±3.33% and 88.81±1.53% at 1, 4 and 8weeks respectively. The mean RBF was significantly higher in the test group than control group at all time intervals. The study outcomes demonstrate that the use of PRF accelerate socket wound healing after tooth extraction as noticed by increased bone fill and reduced alveolar bone width resorption using clinical and radiographic methods.